Pengaruh Harga Tiket, Fasilitas Wisata Dan Kebersihan Lingkungan Terhadap Kepuasan Pengunjung Wisata Sipinsur Kecamatan Paranginan - Sintia Hutasoit; Putra Irwansyah (Journal of Innovative and Creativity, 2026)
The tourism sector is becoming increasingly important in both national and regional development, especially in terms of economic growth. This study examines The Influence of Ticket Prices, Tourism Facilities, and Environmental Cleanliness on Visitor Satisfaction as an Intervening Variable at Sipinsur Tourism Object. The purpose of this research is to determine the extent to which ticket prices, tourism facilities, and environmental cleanliness affect visitor satisfaction. This study uses a quantitative research design with data collected through questionnaires, involving a sample of 100 respondents who have previously visited Sipinsur. The data were processed using SPSS 27, and the analytical techniques applied include multiple linear regression analysis, t-test (partial), and F-test (simultaneous). The results indicate that: (1) Ticket Prices have a significant effect on Visitor Satisfaction, (2) Tourism Facilities have a significant effect on Visitor Satisfaction, (3) Environmental Cleanliness has a significant effect on Visitor Satisfaction, and (4) Ticket Prices, Tourism Facilities, and Environmental Cleanliness collectively have a positive and significant effect on Visitor Satisfaction..